2014
DOI: 10.1007/s10876-014-0778-1
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures and Third-Order Nonlinear Optical Properties of Two-Dimensional Rhombohedral Grid Coordination Polymers: [Cd(imz)3]2(BTC)·0.5H2O and [Cu4(H2O)2(imz)8](BTC)2·7H2O(BTC = 1, 2, 4, 5-benzenetetracarboxylate anion, imz = imidazole)

Abstract: Hydrothermal reactions of 1, 2, 4, 5-benzenetetracarboxylic acid (H 4 BTC) with cadmium acetate and copper acetate in the presence of imidazole (imz) resulted in two new coordination polymers, namely, [Cd(imz) 3 ] 2 (BTC)Á0.5H 2 O 1, [Cu 4 (H 2 O) 2 (imz) 8 ](BTC) 2 Á7H 2 O 2.Two compounds have been characterized structurally using single-crystal diffraction, elemental analysis, and FT-IR spectrum. In compound 1, the hexa-coordinated Cd(II) ions are bridged by BTC to form two-dimensional rhombohedral grid shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…According to obtained results for 6‐Mepic−Co (II)/Cu (II) complexes, 2 − TFMBA and nitrobenzene, these results are remarkable. It is concluded that calculated χ (1) and χ (3) results are coherent with those results of different molecular systems …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…According to obtained results for 6‐Mepic−Co (II)/Cu (II) complexes, 2 − TFMBA and nitrobenzene, these results are remarkable. It is concluded that calculated χ (1) and χ (3) results are coherent with those results of different molecular systems …”
Section: Resultssupporting
confidence: 82%
“…In this respect, it could be considered that the relation between α and n parameters showing the polarization of the compounds through the electromagnetic field of the light . Moreover, the χ (1) parameter called linear susceptibility exhibiting the linear response of the material and the χ (3) parameter called third−nonlinear optical susceptibility defined with Z‐scan technique in the literature were investigated. The larger χ (n) is remarkable to achieve nonlinear optical effect due to the lower value of the strength(s) of the applied electric field(s) and the shorter the path length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to building the basis of experimental work containing transition metal complexes of 6-BrpicH ligand without experimental study with Z-scan technique, the χ (1) (linear optical susceptibility) exhibiting the linear response associated with the linear absorption and refractive index and χ (3) (third-order nonlinear optical susceptibility) parameters were investigated without Z-scan technique. [62][63][64][65][66] The larger χ (n) related to the nonlinear optical effect means the lower applied electric field strength and the shorter path length.…”
Section: Linear and Nonlinear Optical Propertiesmentioning
confidence: 99%
“…Our research group has reported a number of coordination polymers constructed from bis(imidazolyl) ligands. The third-order NLO properties of these compounds as films or in solution have been discussed (Zhao, Liu et al, 2014;An et al, 2015;Lian et al, 2015;Zhao et al, 2015a,b;Liu et al, 2016). Interestingly, the third-order nonlinear susceptibilities of these compounds are much larger than those of the pure inorganic semiconductor materials and some polymer materials (Ballesteros et al, 1999;Poornesh et al, 2009;Zhao, Pan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%